Design of CPW fed f-shaped circularly polarized antenna for amateur radio vehicular communications - V. Ramakrishna, T; T.P. Madhav, B; Amulya, D; Sumitra, S; Sai Kumar, A; Rohit, M; Anilkumar, T (International Journal of Engineering and Technology, 2017)
In this paper a compact circularly polarized antenna is proposed to operate in X-band spectrum. The F-shaped monopole element is used as the radiating structure and the closed coplanar-waveguide ground is used on a FR4 substrate. The proposed feeding mechanism with asymmetric ground planes and the three rectangular strips connected to the feed line. The proposed antenna operates with a -10dB reflection coefficient bandwidth from 9.3 GHz to 13 GHz and the circular polarized performance is attained from 9.8 GHz – 11.2 GHz with axial ratio less than 3dB (AR < 3dB). The antenna gain in the boresight direction is found to be achieved as 4.34dB and radiates with a maximum efficiency of 90% which is suited for amateur radio applications in X-band spectrum based vehicular communications.